2010
DOI: 10.1002/pip.941
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the voltage distribution in photovoltaic modules by electroluminescence imaging

Abstract: We introduce an approach to determine the operating voltage of individual solar cells in photovoltaic (PV) modules by electroluminescence (EL) imaging. The highest EL signal of each solar cell is proportional to its operating voltage. Moreover the sum of all operating voltages equals the externally applied module voltage. Thus the operating voltage of individual solar cells is determined from the measured EL signal. The reliability of this relation is verified by measurements on specially prepared PV modules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 3 publications
3
69
0
Order By: Relevance
“…[7,13,[24][25][26] These background images are prone to noise and STE decreasing the quality of EL images after subtraction. For consistent light conditions, both problems can be significantly reduced by taking at least two background images for different exposure times as input to solve ( ) = • + .…”
Section: Dark Current Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,13,[24][25][26] These background images are prone to noise and STE decreasing the quality of EL images after subtraction. For consistent light conditions, both problems can be significantly reduced by taking at least two background images for different exposure times as input to solve ( ) = • + .…”
Section: Dark Current Removalmentioning
confidence: 99%
“…Is was found suitable for qualitative analysis including identification of shunts, pre-breakdown sites, cracks, broken fingers and interconnectors. Quantitative analysis is also possible for effects such as diffusion length, local voltage and series resistance mapping for cells [2][3][4][5] as well as modules [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, this approach idealizes the actual flat field and ignores the individual pixel deviation. Other methods image a 'homogenous' light source at short distance and out of focus of the camera [7,26]. It was reported that even a high resolution LCD flat panel emitting red light at 612 nm can be sufficient for measuring CdTe solar cells with a recombination peak at around 850 nm [28].…”
Section: Best Focus Determinationmentioning
confidence: 99%
“…STE statistics and removal using a conditional minimum is detailed in [23]. [7,13,[24][25][26] As for EL images, these background images are prone to noise and STE decreasing the quality of EL images after subtraction. Both problems can be significantly reduced by taking at least two background images for different exposure times as input to solve ( ) = • + .…”
Section: Best Focus Determinationmentioning
confidence: 99%
See 1 more Smart Citation